Crypto Asset Investing in the Age of Autonomy - Ryan, Jake (Ascent Audio, 2021)
We've seen evidence that a new economic cycle has begun. Technological revolutions come by way of a cluster of new innovations. About a decade ago, you started to see AI, robotics, and IoT (sensors) delivering on automation. That's been powerful, but not transformational. It does not force businesses to fundamentally change how they do business. The last piece of the puzzle is cryptocurrency because it allows us to process and transfer economic value without human intervention. Soon, there will be a global race to build autonomous operations. Businesses and organizations without autonomous operations simply will not be able to compete with those that do because autonomy is the ultimate competitive advantage. Crypto is the mechanism that will accrue value from being the infrastructure for the next digital financial revolution. Crypto Asset Investing in the Age of Autonomy lays out a case that we've begun a new technological revolution similar to the Internet Age of the 1990s. Artificial intelligence, the Internet of Things, robotics, and cryptocurrency are converging to deliver on a new age, what author Jake Ryan calls the Age of Autonomy. Understanding the transformation that's taken place before anyone else can yield enormous investment opportunity. In this book, you'll learn how and why to invest in crypto assets.